STUDENTS’ SELF-DIRECTION IN LEARNING ENGLISH LISTENING SKILLS AT AN ISLAMIC UNIVERSITY - Nursidah; Muhammad Fajaruddin Rachman; Andi Muhammad Yauri (Institut Agama Islam Negeri Bone, 2025)
This study explores how students at an Islamic university engage in self-directed learning (SDL) to enhance their English listening skills and what motivates that engagement. Using a qualitative descriptive design, semi-structured offline interviews were conducted with seven 6th–8th semester English majors (June 16–17, 2025). Data were transcribed, coded, and member-checked. Findings show that students set academic/professional goals (e.g., TOEFL/IELTS, postgraduate study, employability) as well as social/personal goals (e.g., reducing insecurity, building confidence). They select authentic, accessible materials YouTube, podcasts/TED Talks, films, songs, TikTok and employ repetition, note-taking, shadowing, and self-evaluation (e.g., prediction tests), with technology functioning as a central enabler. Key challenges include wavering motivation, focus and consistency, time constraints, and distracting environments; feedback from lecturers/peers and perseverance (personal drive, family support, future aspirations) help sustain progress. Intrinsic (interest, enjoyment, competitiveness) and extrinsic factors (exams, career targets, lecturer cues, peer influence) jointly shape SDL. The study concludes that SDL is vital for listening development when autonomy is supported by purposeful goals, strategic routines, constructive feedback, and technology use. Implications include designing autonomy-oriented tasks, guiding critical use of digital resources, and improving institutional supports (labs, study groups, workshops) to foster lifelong learning.